ONLINE ADVERTISING – AN INFORMATIONAL & COMMUNICATION SPACE FOR THE ENTERPRISE - CONSTANTINESCU, Lucreția Mariana; TĂNĂSESCU, Irina (Annales Universitatis Apulensis Series Oeconomica; Vol 1 No 16 (2014): Annales Universitatis Apulensis Series Oeconomica, 2014)
The informational society is the result of the most spectacular environmental change due to the role of information in society, which obliges the companies that use online advertizing to digitalize their information and individualize their market offers, their messages and means of communication. Online advertising (Internet advertising) “has grown” and developed faster than any other means and the features of the Internet make it an almost ideal means of advertising compared to the other means of information, offering the opportunity of an advertising campaign on the Internet with multiple advantages for the different companies that use of “online advertising”. This paper aims the reasons why companies adopt Internet advertising which exceeds the traditional media as well as the benefits and barriers of the integration of the new tools of the communication policy in Internet marketing because the future of the online communities belongs to the “smart mobs”, able to act in a focused way via the cyberspace relations network established among the consumers of the different companies through repeated contacts with this network.